Understanding Early Later Stone Age technology at a landscape-scale: evidence from the open-air locality Uitspankraal 7 (UPK7) in the Western Cape, South Africa. Issue 3 (3rd July 2017) - Low, Marika; Mackay, Alex; Phillips, Natasha
ABSTRACT: Understandings of past human behaviour in southern Africa are hampered by a site-based approach to prehistoric technological systems that relies on spatially isolated samples from one or a few key 'type-sites'. Lithic technological behaviour, however, was a landscape-scale process with raw material acquisition, reduction, transportation, use, maintenance and discard taking place at varied locations. This study takes a landscape approach to the investigation of Early Later Stone Age (ELSA) technology on the Doring River by exploring two points in what we believe to be one system. It compares data from an open-air lithic scatter from Uitspankraal 7 (UPK7) located on the Doring, the major river and lithic source in the area, with a published rockshelter sample from Putslaagte 8 (PL8) located 2 km from the Doring and 15 km to the northwest of UPK7. Differences between the two assemblages support a scenario in which hornfels blades and flakes were produced at the river and transported into the surrounding landscape, with limited transportation of cores. Intriguingly little evidence of quartz-bipolar reduction was found in the open-air sample at UPK7, raising the possibility that different ELSA technological components were organised in distinct patterns across the landscape. Results suggest that the composition of ELSA assemblages is highly situational, with proportions of quartz and/or bipolar technology, for instance, appearing responsive to local context. Overall, this study highlights the importance of taking a landscape-orientated approach to investigating the nature and cause of continuity and variability in the archaeological record. Such an approach will inevitably lead to a more comprehensive understanding of early LSA technology, behaviour and land-use patterns.